2017
DOI: 10.1093/mnras/stx2583
|View full text |Cite
|
Sign up to set email alerts
|

What made discy galaxies giant?

Abstract: I studied giant discy galaxies with optical radii more than 30 kpc. The comparison of these systems with discy galaxies of moderate sizes revealed that they tend to have higher rotation velocities, B-band luminosities, H masses and dark-to-luminous mass ratios. The giant discs follow the trend log(M HI )(R 25 ) found for normal size galaxies. It indicates the absence of the peculiarities of evolution of star formation in these galaxies. The H mass to luminosity ratio of giant galaxies appears not to differ fro… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
15
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 43 publications
1
15
0
Order By: Relevance
“…They concluded that the gLSB disc of Malin 2 could have been formed because of unusual properties of the dark halo of the galaxy, namely, its large radial scale and low central density. Saburova (2018) came to a similar conclusion for a sample of giant disc HSB galaxies.…”
Section: Introductionsupporting
confidence: 63%
“…They concluded that the gLSB disc of Malin 2 could have been formed because of unusual properties of the dark halo of the galaxy, namely, its large radial scale and low central density. Saburova (2018) came to a similar conclusion for a sample of giant disc HSB galaxies.…”
Section: Introductionsupporting
confidence: 63%
“…The question of the gLSBGs formation remains open (Kasparova et al 2014;Galaz et al 2015;Hagen et al 2016;Boissier et al 2016;Saburova 2018;Saburova et al 2021) despite their importance as a "stress test" for the ΛCDM cosmology. An in-plane major merger of two giant spiral galaxies with fine-tuned orbital parameters can end-up in a system resembling a gLSBG (Saburova 2018). So does a triple major merger with two gas-rich galaxies when a host's hot halo gas cooling is triggered by the cold gas supply from the infalling systems and later forms a giant extended disc (Zhu et al 2018).…”
mentioning
confidence: 99%
“…Only a couple of dozens gLSBGs were found since the discovery of the prototypical galaxy Malin 1 in the 80s by Bothun et al (1987) so they are considered extremely rare. The question of the gLSBGs formation remains open (Kasparova et al 2014;Galaz et al 2015;Hagen et al 2016;Boissier et al 2016;Saburova 2018;Saburova et al 2021) despite their importance as a "stress test" for the ΛCDM cosmology. An in-plane major merger of two giant spiral galaxies with fine-tuned orbital parameters can end-up in a system resembling a gLSBG (Saburova 2018).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Our deep imaging reveals the complex E-mail:saburovaann@gmail.com structure of UGC 1378, including a high-surface brightness (HSB) bulge and disc, and a gLSB disc. In common with other gLS-BGs, UGC 1378 has prominent spiral arms (like Malin 1, Malin 2, UGC 1922, UGC 1382, Boissier et al 2016Galaz et al 2015;Hagen et al 2016;Kasparova et al 2014;Saburova 2018), resembling the Milky Way immersed in a gLSB disc.…”
Section: Introductionmentioning
confidence: 89%